Scalable electric heating paper based on CNT/Aramid fiber with superior mechanical and electric heating properties. (1st November 2021) - Yang, Bin; Ding, Xueyao; Zhang, Meiyun; Wang, Lin
Abstract : The electric heating approach has aroused intense interest due to its high energy-saving and environmental protection. The excellent features of carbon nanotubes (CNTs) make them the ideal materials to develop electric heating materials, while the aggregation of CNTs and inappropriate choices of substrates have severely restricted their practical applications. Herein, we designe a scalable papermaking route involves a co-refining of CNTs and fibers, to continuously fabricate lightweight, strong and flexible electric heating paper based on CNT/PMIA (Poly ( m -phenylene isophthalamide)) fibers. The particular co-refining of CNTs and PMIA fibrid fibers produces the interspersed CNT/fibrid composites that are bonded by tremendous multiple interfacial interactions, which significantly facilitates high retention and uniform distribution of CNTs in paper substrate. The achieved CNT/PMIA paper shows satisfactory flexibility and folding endurance (over 6000 times), ultrahigh electrical conductivity (80 S cm −1 ), outstanding strength (a tensile strength of 30 MPa and a tear index of 59 mN m 2 g −1 ), excellent electric-heating conversion efficiency (a remarkable heating temperature rise of 230 °C under a safe voltage of 20 V within 15 s), attractive consistently cyclic heating capabilities, and ease of processing with designed shapes. Especially, the CNT/PMIA paper with a length of 2000 m is continuously manufactured by a paper machine, which is further applied in the indoor heating, aircraft deicing, and portable heating clothing, demonstrating great potential for emerging next-generation electric heating devices. Graphical abstract: A facile and scalable papermaking approach involves a particular co-refining of CNTs and fibers is proposed to fabricate lightweight, strong, flexible and highly efficient electric heating CNT/PMIA paper, which is further applied in the indoor heating, aircraft deicing, and portable heating clothing, demonstrating great potential for emerging next-generation electric heating devices. Image 1 Highlights: A scalable approach involves co-refining of CNTs and fibers as well as papermaking is proposed. Lightweight, flexible, strong, and highly efficient electric heating CNT/PMIA paper with is fabricated. CNT/PMIA paper is applied in the indoor heating, aircraft deicing, and portable heating clothing. CNT/PMIA paper demonstrating great potential for emerging next-generation electric heating devices.